CROSS-SECTIONAL STUDY ON CAPRINE SARCOPTIC SCABIES IN THE DISTRIC OF Kl LONPROGO - Samkhan Samkhan; Setyawan Budiharta; Wardiarto Darjoprawito; Bambang Sumiarto (Jurnal Sain Veteriner, 1996)
A cross-sectional study of scabies was performed on 2615 goats from 492 small holder farmers, covered aC subdistricts and 40 out of 88 vfllages in Kulanprogo district, Yogyakarta Province. The Objectives of this study is to investigate (a) factors associated with the prevalence of the disease in goat, and (b) the prevalence uf thedisease among goat population in the district A combination of a three stage and duster sampling procedures was used to select the goat. An animal was considered as suffering from scabies if it showed cuaical sign of scabies and positive laboratory finding of Sarcoptes scabieLThe mportant findings of this study include significant association between sarcoptic scabies in the farm and cleanliness of the barn, animal density, new mcoming animal, new annual from outside of the village, intensive barn, separation of younger animal, between barn distance and closed barn. Other factos, Le. altitude, former's formal education and experience of goat raising are not significantly associated with the disease. In the animal level, new incoming animal, clinical signs, previous infestation and age are found to be associated with the occurrence of the disease. No significant association is found between the occurrence of sarcoptic scabies and sex and breed. The prevalence of the disease is found o be 93% (467492) and 73% (205/2615) for farm and animal level, i respectively.